2021
DOI: 10.1002/jbm4.10485
|View full text |Cite
|
Sign up to set email alerts
|

Higher Hand Grip Strength Is Associated With Greater Radius Bone Size and Strength in Older Men and Women: The Framingham Osteoporosis Study

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
(76 reference statements)
4
7
0
Order By: Relevance
“…Muscle strength was primarily associated with cortical thickness and area, which is in line with the previous observation that higher hand grip strength was associated with greater radius bone size and strength in elderly women and men 28 . It is interesting to note that the main effect of muscle strength was on the cortical compartment.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Muscle strength was primarily associated with cortical thickness and area, which is in line with the previous observation that higher hand grip strength was associated with greater radius bone size and strength in elderly women and men 28 . It is interesting to note that the main effect of muscle strength was on the cortical compartment.…”
Section: Discussionsupporting
confidence: 89%
“…Muscle strength was primarily associated with cortical thickness and area, which is in line with the previous observation that higher hand grip strength was associated with greater radius bone size and strength in elderly women and men. 28 It is interesting to note that the main effect of muscle strength was on the cortical compartment. This finding is supported by a previous bedrest study in which only the cortical thickness of the distal tibia was restored by physical activity countermeasures in women.…”
Section: Discussionmentioning
confidence: 99%
“…A similar protective effect of hand grip strength on nonadjacent bones was also found in a Chile study including 1427 adolescent students ( 14) and a small Chinese study including 120 postmenopausal women (33). In terms of adjacent bone, Mclean et al analyzed the Framingham osteoporosis cohort including 1159 participants and found that higher hand grip strength was associated with higher radius bone size and strength but not volumetric BMD (34). The authors speculate that the unaffected BMD may be because larger bone has similar bone mineral content.…”
Section: Discussionsupporting
confidence: 52%
“…In terms of adjacent bone, Mclean et al. analyzed the Framingham osteoporosis cohort including 1159 participants and found that higher hand grip strength was associated with higher radius bone size and strength but not volumetric BMD ( 34 ). The authors speculate that the unaffected BMD may be because larger bone has similar bone mineral content.…”
Section: Discussionmentioning
confidence: 99%
“…These associations are consistent with previous studies. 22,[43][44][45] This suggests that lower muscle function test performance may be "indirect" indicators of low bone strength (ie, impaired bone geometry and low aBMD). Furthermore, 5-STS and dynamometry are simple, quick, low cost, easy to apply, have good reproducibility, and can be used in a variety of clinical settings, making them ideal for outpatient clinics.…”
Section: Discussionmentioning
confidence: 99%